Gender Equality and Power in Romania - PROFIROIU Alina-Georgiana; NASTACĂ Corina-Cristiana (Applied Research in Administrative Sciences)
The present research investigates Romania’s position in the Gender Equality Index and the progress registered by the country concerning women’s representation in elected and appointed political positions in the 2003-2020/2021 period. The main objective of the study is to create a comprehensive picture regarding political leadership in Romania and the country’s position and progress in the European rankings regarding gender equality in positions with high power of decision. The study revealed that regarding political power, in Romania, women continue to be underrepresented as ministries, deputies, senators, members of the County Councils and mayors. The gender balance is far from being achieved and Covid-19 pandemic might widen the gender gap which in this field, is already high. Men continue to be elected and appointed in these important positions and hold the real power of decision and the gender equality objective was not fulfilled.